Filsynkronisering i realtid - Plugin til Eclipse för synkronisering av programkod - Källtén, Magnus; Strömner, David (My University, 2015)
The intention of this project was to create an improvement for code collaboration. Code collaboration is something developers often struggle with and none of today’s programs and methods remove the problem entirely. A solution is to introduce a program that runs in the background that can modify files’ content. This proposed program would allow developers to connect to each other to share and work simultaneously on the same projects and files. The program we developed became a plugin to the IDE (Integrated Development Environment) Eclipse and it can be used by two developers to write in shared files while being able to see what the other developer is writing in real time. The program we developed has the potential to improve the way code is developed in the near future.
Keywords: Data- och informationsvetenskap; Computer and Information Science